2013
DOI: 10.1021/jp400592x
|View full text |Cite
|
Sign up to set email alerts
|

NbC Nanowire-Supported Pt Nanoparticles as a High Performance Catalyst for Methanol Electrooxidation

Abstract: NbC nanowires (NWs) have been successfully synthesized by a bamboo-based carbon-thermal method and used as potential platinum catalyst support for direct methanol fuel cells (DMFCs). The NbC NWs show a highly oriented growth behavior, high electrical conductivity, and outstanding oxidation resistance. Well-deposited platinum (Pt) nanoparticles with the average size of about 6 nm were highly dispersed on the surface of the NbC NWs via sodium borohydride reduction method. Compared with conventional Pt/C (Vulcan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…Figure 4a illustrates the typical CV curves of Pt 0.54 /NiFe-LDH/rGO, Pt 0.12 /Ni(OH) 2 /rGO and commercial Pt/C. On the basis of integrated hydrogen desorption region 31 , the calculated result showed that the ECSA values of Pt catalysts on Pt 0.54 /NiFe-LDH/rGO (609.01 cm 2 mg −1 ) and Pt 0.12 /Ni(OH) 2 /rGO (767.62 cm 2 mg −1 ) were higher than that of commercial Pt/C (498.86 cm 2 mg −1 ). And given that the comparatively low loading amount and higher dispersity of Pt NPs, as verified by the ICP-AES analysis, Pt 0.12 /Ni(OH) 2 /rGO (Pt concentration, 28.53 µg mL −1 ) ternary hybrids showed slightly higher electrocatalytic activity than that of Pt 0.54 /NiFe-LDH/rGO (Pt concentration, 146.80 µg mL −1 ) during MOR.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4a illustrates the typical CV curves of Pt 0.54 /NiFe-LDH/rGO, Pt 0.12 /Ni(OH) 2 /rGO and commercial Pt/C. On the basis of integrated hydrogen desorption region 31 , the calculated result showed that the ECSA values of Pt catalysts on Pt 0.54 /NiFe-LDH/rGO (609.01 cm 2 mg −1 ) and Pt 0.12 /Ni(OH) 2 /rGO (767.62 cm 2 mg −1 ) were higher than that of commercial Pt/C (498.86 cm 2 mg −1 ). And given that the comparatively low loading amount and higher dispersity of Pt NPs, as verified by the ICP-AES analysis, Pt 0.12 /Ni(OH) 2 /rGO (Pt concentration, 28.53 µg mL −1 ) ternary hybrids showed slightly higher electrocatalytic activity than that of Pt 0.54 /NiFe-LDH/rGO (Pt concentration, 146.80 µg mL −1 ) during MOR.…”
Section: Resultsmentioning
confidence: 99%
“…Usually high-temperature solid state routes are utilized to prepare a nitride 110 or carbide support. 111 Subsequent deposition of noble metal NPs afforded excellent catalysts, in a wide range of applications, as exemplified by electrocatalysts. Recently, a colloidal route was established for nitride 112 and phosphide 113 NCs, which opened up the possibility for constructing nanointerfaces between these binary compounds and metals.…”
Section: Metal and Non-oxide Interfacesmentioning
confidence: 99%
“…Other transition‐metal carbides, including TiC,106 NbC,107 VC,108 and Mo 2 C,109 have also been used as Pt supports. For example, NbC nanowires have recently been synthesized by using a bamboo‐based carbothermal method and used as Pt supports for direct methanol fuel cells (DMFCs) 107. 1D NbC NWs showed highly oriented growth behavior, high electrical conductivity, and outstanding oxidation resistance, thereby leading increased activity and excellent stability towards the MOR.…”
Section: Development Of Advanced Supporting Materialsmentioning
confidence: 99%